Application of Wordwall-Assisted Game Based Learning to Improve Science Learning Outcomes in Elementary Schools - Yudiono, Udik; Patmawati, Devi; Pratiwi, Wahyu (Actual Insight : Lembaga Penelitian Pengembangan, Penerbitan dan Publikasi, 2025)
The low mathematics learning outcomes at State Elementary School Tanjungrejo 3 Malang are a concern in an effort to improve the quality of learning. One of the reasons is the lack of variety of learning models that are interesting and able to motivate students to actively engage in the learning process. To overcome this, this study aims to improve the mathematics learning outcomes of grade V students through the application of the Game Based Learning model assisted by Wordwall media. Wordwall is a digital platform that provides various types of interactive educational games that can be accessed online and offline. The research method used is Class Action Research (PTK) with two cycles, each consisting of planning, implementation, observation, and reflection stages. Data was collected through learning outcome tests and student activity observation sheets, then analyzed descriptively, quantitatively, and qualitatively. The results showed a significant increase in student learning outcomes, with the average score increasing from 69.63 in the pre-cycle to 88.89 in the second cycle. The percentage of student learning completeness has also increased from 41% to 93%. In addition, student involvement in learning also increases with the use of interactive Wordwall game media . These findings show that the application of the Wordwall-assisted Game Based Learning model is effective in improving students' mathematics learning outcomes.